Ride the pink horse - Hughes, Dorothy B. 1904-1993; Skinner, Frank 1897-1968 (The Criterion Collection, 2015)
A tough-talking former GI comes to a small New Mexico town to shake down a gangster who killed his best friend; events turn out neither as planned nor at all well
Bildformat 1.37:1
Orig.: USA 1947
Enth. audio commentary featuring film noir historians Alain Silver and James Ursini ; new interview with Imogen Sara Smith, author of "In lonely places: film noir beyond the city" ; "Lux Radio Theatre" adaptation of the film from 1947, features Robert Montgomery, Wanda Hendrix, and Thomas Gomez ; an essay by filmmaker and writer Michael Almereyda